Leveraging the Thermoresponsiveness of Poly(N-Isopropylacrylamide) Copolymers as a Sensing Tool for Perfluorooctane Sulfonate - Savage, Dustin T. (Analyst, 2021)
Due to mounting evidence of the negative health effects of persistent perfluoroalkyl acids (PFAAs) with long (i.e., >C(7)) tails, there is a need for convenient systems capable of sensing these contaminants at dilute aqueous concentrations. To address this concern, a thermoresponsive polymeric network composed of poly(N-isopropylacrylamide) copolymerized with fluorinated comonomers was studied to characterize the gel’s physical response to fluorosurfactants in solution. Incorporating fluorinated comonomers into the polymer backbone raised their swelling in fluorocontaminant solutions relative to water – gels synthesized with 10.0 mol% 2,2,2-trifluoroethyl acrylate (TFEA) displayed a heightened maximum water-analyte swelling difference of 3,761 ± 147% compared to 3,201 ± 466% for non-fluorinated gels in the presence of 1 mM tetraethylammonium perfluorooctane sulfonate (TPFOS). The normalized area under the curve for gels with 12.5 mol% TFEA was further raised to 1.77 ± 0.09, indicating a broadened response window for the contaminant, but at the cost of reducing the overall swelling ratio to 3,227 ± 166% and elongating the time required to reach swelling equilibrium. Overall, a copolymer fed with 10.7 mol% TFEA was predicted to maximize both the swelling and response window of the polymer toward TPFOS. Equilibration times followed a logarithmic increase as the percentage of comonomer was raised, noting gradual fluorosurfactant penetration into the gels impeded by initial gel compaction caused by the addition of fluorinated comonomers. Comparative study of gels containing 1H,1H,7H-dodecafluoroheptyl acrylate, TFEA, or 1,1,1,3,3,3-hexafluoroisopropyl acrylate identified careful selection of fluorinated comonomers and their feed ratios as useful tools for tailoring the network’s swelling response to TPFOS.